Communication Marketing Strategy For Mandalika Special Economic Zone As The 2018 Post Earthquake Priority Destination By The West Nusa Tenggara Tourism Office - sri hermalia wulandari (JCommsci - Journal Of Media and Communication Science, 2019)
ABSTRACTThe earthquake that occurred in 2018 had an impact on the tourism sector in West Nusa Tenggara, which caused a decrease in the number of tourist visits by 69.18% from 2017. The Mandalika Special Economic Zone as a minimal destination affected by the earthquake became a bright spot for the West Nusa Tenggara Tourism Office tourists to return to West Nusa Tenggara. The purpose of this study was to find out the Mandalika Special Economic Zone Marketing Communication Strategy as the 2018 Post Earthquake Priority Destination by the West Nusa Tenggara Tourism Office. This study used a descriptive method with a qualitative approach. The results of this study indicate that after the 2018 earthquake, the  West Nusa Tenggara Tourism Office carried out a communication strategy planning process through 4 (four) steps namely Communication Target Analysis, Message Strategy, Establishing Methods and Media Selection. In destination promotions also the Tourism Office emphasizes aspects of Branding, Advertising and Selling. To strengthen destination promotion, the Tourism Office of West Nusa Tenggara conducts publications and promotions through Paid Media (local and national print and electronic media), owned media (websites), social media (Twitter, Facebook and Instagram). In implementing the strategy, the Tourism Office cooperates with 5 (five) elements of Pentahelix, namely the Academics, Business, Community, Government and Media partiesKewords: Communication Strategy; Tourism Destinations; Marketing